2019
DOI: 10.34218/ijm.10.6.2019.026
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Human Capacities of High and Low Performers of Public Sector Manufacturing Industry in India

Abstract: Background: Public Sector Manufacturing Industry in India has well dominated the culture of satisfactory under-performance in the past, wherein even low performance is seen as satisfactory as a Governmental promotion strategy. However, with time, the Public Sector"s monopolistic existence has witnessed entry of new private players as their competitors and compelled them to perform at an equal platform, if not better. The change has geared the overall Management perspective/ strategy of Manufacturing Industry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Las instituciones públicas deben ser efectivas en la atención integral al ciudadano para lo cual deben tener las habilidades necesarias para su desenvolvimiento diario (Nankya-Mutyoba et al, 2022), por lo que se debe capacitar a todo los agentes necesarios (Estrada Molina et al, 2015) no solo en habilidades básicas sino también en habilidades de gestión y muy importante el manejo de nuevas tecnologías de información (Carter et al, 2021). Ya que las capacidades humanas que impulsan los resultados organizacionales están siendo reconocidos y las organizaciones gastan cada vez más en mejorar las Capacidades Humanas Intrínsecas de sus empleados, Teniendo en cuenta la singularidad de cada individuo (Jain & Singh, 2019). Se determina que empleando la capacitación a menudo se considera esencial para incorporar prácticas de gestión del desempeño en las organizaciones, pero pocos estudios vinculan directamente la capacitación con programas a cambios posteriores en resultados organizacionales .…”
Section: Discussionunclassified
“…Las instituciones públicas deben ser efectivas en la atención integral al ciudadano para lo cual deben tener las habilidades necesarias para su desenvolvimiento diario (Nankya-Mutyoba et al, 2022), por lo que se debe capacitar a todo los agentes necesarios (Estrada Molina et al, 2015) no solo en habilidades básicas sino también en habilidades de gestión y muy importante el manejo de nuevas tecnologías de información (Carter et al, 2021). Ya que las capacidades humanas que impulsan los resultados organizacionales están siendo reconocidos y las organizaciones gastan cada vez más en mejorar las Capacidades Humanas Intrínsecas de sus empleados, Teniendo en cuenta la singularidad de cada individuo (Jain & Singh, 2019). Se determina que empleando la capacitación a menudo se considera esencial para incorporar prácticas de gestión del desempeño en las organizaciones, pero pocos estudios vinculan directamente la capacitación con programas a cambios posteriores en resultados organizacionales .…”
Section: Discussionunclassified
“…Land mentioned that many teams often assume that employees have the necessary knowledge of the project, but such assumption may lead to team inequality, suggested that team members' technical ability should be improved through collective team training, and stressed the importance of practical practice for team cooperation [75]. Singh argued that executives with higher intrinsic interpersonal competence (including learning ability, conceptual ability, relational ability, action ability, spiritual intelligence) exhibit higher levels of job performance in the Indian public sector manufacturing industry [98]. Chin and Yusof mainly focused on how to improve employees' emotional intelligence to improve job satisfaction and how it has an impact on enterprise performance [82].…”
Section: Improving Organizational Performance Approachesmentioning
confidence: 99%